楚科奇海—加拿大海盆表层沉积物中的粘土矿物 - 张德玉; 高爱国; 张道建 (2008)
楚科奇海—加拿大海盆表层沉积物中主要存在3种粘土矿物组合:1)伊利石—高岭石—绿泥石—蒙皂石,仅见于加拿大海盆北部;2)伊利石—绿泥石—蒙皂石—高岭石,主要见于楚科奇海中部;3)伊利石—绿泥石—高岭石—蒙皂石,普遍见于研究区内除上述两海区以外的广大区域。就各粘土矿物的区域变化而言,总体上由楚科奇海向加拿大海盆,伊利石和高岭石呈含量增加趋势,绿泥石和蒙皂石含量呈减少趋势。根据粘土矿物的质量分数和粘土矿物间比值的区域变化,可大体以(74°30′N,175°W)和(71°30′N,150°W)两点连线为界,将研究区分为南、北两个明显不同的粘土矿物分区:南区以绿泥石和蒙皂石含量较高为主要特征,其中S/I和S/K普遍较高、而K/I和K/CH则普遍较低;北区则以伊利石和高岭石含量较高为主要特征,其中S/I和S/K普遍较低,而K/I和K/CH则普遍较高。粘土矿物的这种分布格局和区域变化表明,在北冰洋的楚科奇海—加拿大海盆海域,不论是粘土矿物的来源还是其分布变化的控制因素,都存在着明显的南、北之别:在该海域的南部,粘土矿物主要来源于阿拉斯加的岩石风化产物、育空河的入海物质以及东西伯利亚海沿岸主要河流的入海物质,其分布主要受来自太平洋的水流结构和西伯利亚沿岸流所控制;而在该海域的北部,粘土矿物则主要来源于加拿大马更些河的入海物质和由北冰洋欧亚海盆扩散而来的细粒物质,其分布主要受北冰洋的跨极漂流、来自大西洋的水流结构以及波弗特涡流等所控制。 Three types of clay mineral assemblage were identified in surface sediments from the Chukchi Sea and Canadian Basin,among them,the illite-kaolinite-chlorite-smectite assemblage was found only in the northern Canadian Basin,the illite-chlorite-smectite-kaolinite assemblage was mainly found in the central Chukchi Sea,and the illite-chlorite-kaolinite-smectite assemblage is widely distributed in the rest part of the study area.Generally,the illite and kaolinite contents show an increasing trend from the Chukchi Sea toward the Canadian Basin,and the chlorite and smectite contents show a decreasing trend.If taking the line connecting point(74°30′N,175°W) and point(71°30′N,150°W) as a demarcation line,the study area can be divided into two clay mineral provinces,the south province and the north province,the south pro-vince is characterized with higher contents of chlorite and smectite,higher ratios of S/I and S/K and lower ratios of K/I and K/CH;and the north province is characterized with higher contents of illite and kaoli-nite,lower ratios of S/I and S/K and higher ratios of K/I and K/CH.It is shown from the clay mineral distributions and variational trends that the clay mineral sources and the factors controlling their distributions in the south province and the north province are different from each other.The clay minerals in the south province are derived mainly from the weathering products of Alaska's rocks and the sediments delivered by the Yukon River and the rivers along the coast of the East Siberian Sea,and the clay mineral distributions in the south province are controlled mainly by the Siberian Coastal Current and the flowing structure of the Pacific Water entering into the Arctic Ocean;and the clay minerals in the north province are derived mainly from the sediments delivered by the Mackenzie River of Canada and the fine-grained sediments dispersed from the Eurasian Basin of Arctic Ocean,and the clay mineral distributions in the north province are controlled mainly by the Transpolar Drift,the flowing structure of Atlantic Water and the Beaufort Gyre in the Arctic Ocean. 国家自然科学基金重点项目——楚科奇海沉积物中古环境变化的地球化学响应(40376017);; 科技部中国—丹麦合作研究项目——东海晚第四纪高分辨率的古环境和古气候演变序列研究(2002DFG00034)